Application of nature based algorithm in natural resource management - Barman, Rabindra Nath; Majumder, Mrinmoy (Springer Netherlands, 2013)
The book describes the utility and efficiency of nature based algorithms in optimization, classification and simulation of natural resource management problems.The book deals with climate change, hydrology, renewable energy and natural ecosystems and tries to find solution to its common uncertainties so that proper mitigation steps can be undertaken to reduce both quantity and probability of such anomalies. The book aims to propose some methodologies which can help related engineers and planners to mitigate the common abnormalities that exist to derail the equilibrium of a natural ecosystem and its biotic as well as abiotic components.